Draft genome sequences of four methicillin-resistant Staphylococcus aureus strains (M080_2017, M106_2017, M181_2017, and M191_2017), isolated from a Malaysian teaching hospital - Mia, Yang Ang; Mohamad Farook, Nurul Amirah; Kamarudin, Norhidayah; Su, Datt Lam; Di Gregorio, Sabrina; Tengku Jamaluddin, Tengku Zetty Maztura; Nathan, Sheila; Abdul Samat, Muttaqillah Najihan; Argimón, Silvia; Hui, min Neoh (American Society for Microbiology, 2022)
Draft genome sequences were obtained for four methicillin-resistant Staphylococcus aureus (MRSA) strains isolated from various wards of the Hospital Canselor Tuanku Muhriz (HCTM), Kuala Lumpur, Malaysia, in 2017. Using different bioinformatics tools, we annotated the draft genomes and identified multiple antimicrobial resistance genes.